Strategi Kecamatan Ngrayun Kabupaten Ponorogo Mengatasi Pernikahan Dini - Sari, Indah Ayu Mila; Purba, Iman Pasu Marganda Hadianto (Kajian Moral dan Kewarganegaraan, 2026)
This study discusses the practice of early marriage carried out by men and women who are not yet old enough or have not reached a certain level of maturity in Ngrayun District, Ponorogo Regency. This study aims to determine the factors behind the occurrence of early marriage and to determine the strategy of Ngrayun District, Ponorogo Regency in overcoming early marriage. This type of research uses a descriptive method with a qualitative approach. The informants in the study were the Head of Ngrayun District, the KUA of Ngrayun District and perpetrators of early marriage who live in Ngrayun District. The data collection techniques include observation, in-depth interviews, and documentation. The results of the study indicate that the high number of early marriages is due to several factors, namely feelings of mutual consent between partners (love), religious views, plurality of laws governing marriage, parental pressure, pregnancy outside of marriage, traditions that develop in society, level of education, and the influence of technological developments. The government's strategy in this case is carried out through several methods, namely Guidance for School-Age Youth (BRUS), socialization, Marriage Guidance (BIMWIN), Nahdatul Ulama Family Welfare Movement (GKMNU), utilization of social media and Guidance for Marriage-Age Youth (BRUN). The strategy carried out is moving to the development stage. However, the results achieved have not been in accordance with the desired mission in overcoming problems that occur in the long term. Several factors inhibiting the success of this strategy lie in the delivery of the program delivered, the content of the program material, and the construction of society in Ngrayun District.